Poetic Experience And Sufi Manifestation In The Diwan "seasons Of The East" By Mohamed Bennis - Aouadi, Ghania; Maghrebi, Mohamed Reda (El Omda in Linguistics and Discourse Analysis, 2024)
The beauty of self-understanding is manifested in the collection "Seasons of the East" by Mohamed Beniss through his creative interaction with Sufi poetic worlds. The poet expresses his philosophical and spiritual vision in an innovative style. This interaction is evident through the poet's ability to encode linguistic concepts and redefine them in a renewed manner, making the collection open to reception and interpretation. The collection is part of an intellectual and cultural journey that explores the heritage of Arabic poetry with a modern perspective, highlighting Sufi poetry as a fundamental element contributing to the construction and shaping of cultural and artistic consciousness. This reflects the transformations and developments in poetic and cultural thought in contemporary Arab society.